البناء العشوائي على الأرض الزراعية في القانون العراقي - د. أسامة محمد سعيد (PROSPECTIVE RESEARCHES, 2023)
All untidily scattered buildings obstruct the agricultural operations, because these buildings create undesirable opportunities which open gates of expenditure and damages, accounting for these buildings need roads, electricity, water, protection and all other social services, and as a result of this kind of constructions the bad cases of social, healthy and cultural will increase. The Iraqi legislator didn't allow using agricultural land for non– agriculture with the exception of permission of specialized buildings concerning agriculture only. When some decisions had been issued by the abolished Council of Revolution command permitted the limited dwelling constructions on the agricultural land, more people competed to swallow the land without taking care of the visible future and national dimention. Situation got worst during the years of the blockade, and after American occupation. There were no effective efforts comprise the volume of the problem. A matter which requires a real protection for arable land through obliged legislation, in addition to re-working of some abolished laws, such as law of agricultural land tax, No. 60 in the year 1961, in order that all owners and the others who have working rights in lands can act together for agricultural exploitation without delay, whatever are the circumstances.